Employee Commitment, Engagement, and Environment in Performance Achievement: Komitmen, Keterlibatan, dan Lingkungan Kerja Karyawan dalam Pencapaian Kinerja - Indriyanto , Fahril; Firdaus, Vera (Universitas Muhammadiyah Sidoarjo, 2025)
(General background) Employee performance is a crucial element determining organizational success, particularly in competitive service sectors such as transportation and logistics. (Specific background) PT. Sentosa Abadi Transport faces challenges related to employee collaboration, trust, and workspace conditions, which potentially affect productivity and performance outcomes. (Knowledge gap) Previous studies mainly examined two factors—organizational commitment and work environment—without integrating job engagement as a contributing dimension. (Aims) This study aims to analyze how organizational commitment, job engagement, and work environment relate to employee performance in an integrated framework. (Results) Using a quantitative approach with 100 respondents and SPSS-based regression analysis, findings show all three variables have a positive and significant relationship with employee performance, both partially and simultaneously. (Novelty) The inclusion of job engagement alongside commitment and environment provides a more comprehensive understanding of performance drivers within logistics organizations. (Implications) These results emphasize the need for management strategies that strengthen employee commitment, foster engagement, and improve work conditions to achieve sustainable performance growth. Highlights: Integrates three major HR variables into one performance model. Confirms significant positive relationships across all dimensions. Offers managerial insights for enhancing logistics workforce productivity. Keywords: Organizational Commitment, Job Engagement, Work Environment, Employee Performance, Human Resource Management